‘Basically, I’m gonna ask you a load of questions’: Cautioning exchanges in police interviews with adolescent suspects - Heini, Annina (Language and Law / Linguagem e Direito, 2023)
The police caution in England and Wales is a compulsory element of every police interview that informs suspects of their right to silence and outlines the concept of adverse inference. This research draws on authentic data from interviews with 17- and 18-year-old suspects from two English police forces, analysing how the cautioning exchanges are negotiated while considering suspects’ ages and legal statuses as children and adults, respectively. Taking an inductive approach rooted in conversation analysis, the findings reveal an overall tendency for interviewers to explain the caution directly after reciting it, thereby acting on a presumption of suspects’ non-comprehension. It is also considered how the (discursive) presence of appropriate adults in interviews with juveniles can complicate the interactions. The study sheds light on the experiences of an under-researched group of interviewees and discusses the implications